Insight on the use of Cohesive Zone Models for Impact Strength Analysis of Adhesive Joints - D. M. S. R. B. Machado; R. D. S. G. Campilho (Technological Innovation in Engineering Research Vol. 3, 2022)
Adhesive bonds are increasingly becoming an alternative to engineering applications. The increasing use of this type of joining requires suitable tools to support the design process. Among the damage criteria or models associated with the Finite Element Method, cohesive zone models (CZM) are highly effective, combining strength and toughness parameters to predict the performance of adhesive joints. In many practical situations, such as vehicle crashes, adhesive joints are subjected to impact loads. The major goal of this research is to study the influence of the cohesive parameters in predicting the strength of single-lap joints (SLJ) subjected to impact loads. By altering each of these characteristics while keeping the others constant, the influence of the cohesive parameters was investigated. The Araldite® AV138 (high stiffness) and Nagase Chemtex® XNR6852 E-2 (high toughness) adhesives were chosen to study the effect of differing adhesive qualities. It was found that CZM properly predicts joint impact strength and that CZM settings have a significant impact on joint strength.